Dynamic modeling and flexible control of combined heat and power units integrated with thermal energy storage system - Xiaoyu Wang; Lijiang Dong; Qing Zhu; Yongji Li; Hongzhi Han; Jiahao Liang; Bingde Duan (Energy Reports, 2023)
The high percentage of renewable energy connected to the grid requires high operational flexibility of combined heat and power (CHP) units. As two products of the CHP units, electricity and heat are coupled, making it challenging to achieve coordinated control. The thermal energy storage (TES) system can smooth out the fluctuations in heat load demand by storing or releasing heat, thus aiding in the decoupling and coordinated control of electricity and heat. In this paper, an optimized control strategy of CHP units integrated with the TES system is proposed to improve the units’ operating flexibility. First, according to the operating mechanism, the dynamic models of the CHP unit and the TES system are established. On this basis, considering the heat source steam active response based on the linear quadratic regulator and the heat-supply support of the TES system, the boiler-turbine-heating-storage coordinated control system of a CHP unit is designed. The simulation experiment is conducted in a 300 MW CHP unit. The results show that compared with the conventional control strategy, the MAE, MAPE, MSE, and RMSE indicators of the electrical power output are decreased by 45.88%, 45.28%, 71.95%, and 47.04%, respectively.